Changes in the Jumping Capacity in the "Bosco" Test After the Application of Strength Training (Based on the Contrast Method in Subjects Between 50 and 70 Years of Age With Different Physical Fitness Levels) - J.M. González; M. Delgado; M. Vaquero; O. Contreras (European Journal of Human Movement, 2010)
The aim of this study is to examine the differences of force production in 50 -70 year old athletes and active subjects, both before and after the strength training and, on the other hand the effects of such a 16 week strength training on height jump in bosco protocol (SJ, CMJ, DJ). The strength training is based on the alternative use of light and heavy leads. A population sample of 23 subjects was studied which was divided into two groups (athletes n=11- and active subjects n=12-) and two test were performed, before and after strength training (independent variable). The dependent variables were maximum jumping height in Bosco protocol (SJ, CMJ, DJ) measured with pressure platform (lisenced faculty of Physical activity and sport sciences, Granada University). The results suggested that the maximum jumping height in SJ, CMJ, DJ is higher in athletes than in active subjects of the same ages. A strength training based on heavy and light load contrast caused both groups to significantly improve their maximum jumping height. To sum up, we suggest that an improve on force production can be achieved by a 16-week strength training programme based on a one-session heavy and light loads contrast method. KEY WORDS: training, contrast, aging, strength